Nurses' Experience in Providing Patient Services with HIV/AIDS - Fenska Narly Makualaina; Fathia F I Said; Nofita Dewi Kok Mesa (GLOBAL HEALTH SCIENCE GROUP, 2024)
The never-ending problem of HIV AIDS is a phenomenon that deserves to be investigated and followed up by all parties, especially health workers as implementers of prevention, control, and treatment efforts in the health service environment. Method: This study uses a descriptive qualitative research design with a phenomenological approach. The number of participants was 5 health workers who work at the Puskesmas Harapan. The research instrument used in-depth interviews, field notes and documentation which were then analyzed by determining keywords, categories and themes. Results: The results of the study found that the experience of health workers in caring for HIV AIDS patients was expressed in the form of empathy, lack of empathy, and fear caused by various other supporting factors such as limited availability of health services and patient non-compliance in ARV treatment. Conclusion : It can be concluded that the experience of health workers needs to get support from various parties including patients, patient families, and health care facilities.